Strategies for Aging in Place - Suzanne Dupuis-Blanchard; Odette N. Gould; Caroline Gibbons; Majella Simard; Sophie Éthier; Lita Villalon (Global Qualitative Nursing Research, 2015)
For healthy and independent older adults, aging in place can be seen as identical to any other adult living at home. Little is known about how frail seniors, particularly those who speak a minority language, manage the challenges of aging in place. The present qualitative descriptive study explores the strategies that Canadian French-speaking seniors have put in place to counter their loss of independence and promote their ability to stay in their home. Semistructured individual interviews were conducted with 39 older adults and transcribed, followed by content analysis to identify common themes related to study objectives. Six themes emerged in response to strategies described for aging in place. Findings reveal the limited extent to which language issues were perceived as a barrier by participants. In conclusion, the results of this study provide us with fruitful insights to guide community nursing practice, future research, and public policy.